Electroluminescence in alternating copolymers with the acetylene unit - Kim, DY; Hong, JM; Kim, JK; Cho, HN; Kim, CY (WILEY-V C H VERLAG GMBH, 1999)
2,7-diethynyl-9,9'-di-n-hexylfluorene and 2,7-dibromo-9,9'-di-n-hexyrfluorene were alternately bonded with each other by a Heck reaction to produce poly(9,9'-di-n-hexyl-2,7-fluorenyleneethynylene). The alternating copolymer emitted blue color with the peak maximum at 475 nm on excitation either at 340, 365 or 400 nm. The principal emission maximum shifted to 425 nm on excitation at 340 nm when the polymer was blended with polyvinylcarbazole(PVK). Light-emitting diodes (LEDs) fabricated with the alternating copolymer sandwiched between indium-tin oxide glass and Al emitted a light with the peak maximum at 550 nm. The peak maximum shifted to 425 nm when the copolymer was blended with PVK with the blending ratios between 5 to 20% of the emissive copolymer.